KONSEPTUAL RPP AKIDAH AKHLAK BERBASIS DEEP LEARNING DAN KURIKULUM BERBASIS CINTA (KBC) - Candra Adlani; Sitie Khadizah; Patimah Patimah; Abdullah Abdullah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The development of Akidah Akhlak learning devices still faces challenges in integrating cognitive, affective, and spiritual aspects in a balanced manner. Most lesson plans (RPP) remain focused on administrative planning aspects, thus requiring the development of a learning design that is more meaningful, humanistic, and oriented toward students’ character formation. This study aims to examine and formulate a concept for developing a Lesson Plan (RPP) for the Akidah Akhlak subject by integrating the Deep Learning approach and the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC). This research employed a qualitative approach using a library research method. Data were obtained from scientific articles indexed in Google Scholar, DOAJ, and Portal Garuda published during the 2016–2026 period, as well as policy documents from the Ministry of Religious Affairs, particularly the Decree of the Minister of Religious Affairs (KMA) Number 1503 of 2025. Data were analyzed using content analysis techniques through the processes of data reduction, categorization, synthesis, and conclusion drawing to develop a conceptual framework for RPP development. The findings indicate that the integration of the Deep Learning approach, which includes mindful learning, meaningful learning, and joyful learning, with the principles of KBC emphasizing compassion, respect for students’ dignity, and character development, can produce a more holistic RPP design. The integration of these two approaches results in a conceptual RPP framework that includes the formulation of learning objectives, learning strategies, learning experiences, assessment, and reflection oriented toward meaningful, humanistic, and student-centered learning. The contribution of this study lies in formulating a conceptual framework that integrates Deep Learning and KBC in the development of Akidah Akhlak RPP, which can serve as a reference for developing Islamic Religious Education learning devices in accordance with the direction of current curriculum implementation. ABSTRAK Pengembangan perangkat pembelajaran Akidah Akhlak masih menghadapi tantangan dalam mengintegrasikan aspek kognitif, afektif, dan spiritual secara seimbang. Sebagian besar RPP masih berfokus pada aspek perencanaan administratif, sehingga diperlukan pengembangan desain pembelajaran yang lebih bermakna, humanis, dan berorientasi pada pembentukan karakter peserta didik. Penelitian ini bertujuan mengkaji dan merumuskan konsep pengembangan Rencana Pelaksanaan Pembelajaran (RPP) mata pelajaran Akidah Akhlak yang mengintegrasikan pendekatan Deep Learning dan Kurikulum Berbasis Cinta (KBC). Penelitian menggunakan pendekatan kualitatif dengan metode studi pustaka (library research). Data diperoleh dari artikel ilmiah yang terindeks pada Google Scholar, DOAJ, dan Portal Garuda periode 2016–2026 serta dokumen kebijakan Kementerian Agama, khususnya KMA Nomor 1503 Tahun 2025. Data dianalisis menggunakan teknik analisis isi (content analysis) melalui proses reduksi, kategorisasi, sintesis, dan penarikan kesimpulan untuk menghasilkan kerangka konseptual pengembangan RPP. Hasil kajian menunjukkan bahwa integrasi pendekatan Deep Learning yang meliputi mindful learning, meaningful learning, dan joyful learning dengan prinsip KBC yang menekankan kasih sayang, penghargaan terhadap martabat peserta didik, serta pembentukan karakter mampu menghasilkan desain RPP yang lebih holistik. Integrasi kedua pendekatan tersebut menghasilkan kerangka konseptual RPP yang mencakup perumusan tujuan pembelajaran, strategi pembelajaran, pengalaman belajar, asesmen, dan refleksi yang berorientasi pada pembelajaran bermakna, humanis, dan berpusat pada peserta didik. Kontribusi penelitian ini terletak pada perumusan kerangka konseptual integrasi Deep Learning dan KBC dalam pengembangan RPP Akidah Akhlak yang dapat menjadi acuan pengembangan perangkat pembelajaran Pendidikan Agama Islam sesuai dengan arah implementasi kurikulum terkini.